How Do Developmental and Accommodative HRM Enhance Employee Engagement and Commitment? The Role of Psychological Contract and SOC Strategies. (20th May 2013) - Bal, P. Matthijs; Kooij, Dorien T. A. M.; De Jong, Simon B.
Abstract In the context of the changing workforce, this study introduced two perspectives on HRM and distinguished universalistic developmental HRM from contingent accommodative HRM. We predicted two separate pathways for the effects on two employee outcomes: work engagement and affective commitment. We expected that developmental HRM would universally relate to employee outcomes by rebalancing the psychological contract between the employee and organization into a less transactional to a more relational contract. We also predicted that accommodative HRM would relate to outcomes only when fulfilling specific needs of employees, associated with their selecting, optimizing, and compensating strategies. Results of a multilevel study among 1058 employees in 17 healthcare units fully supported our expectations regarding the role of the psychological contract. Additionally, we found support for the expected roles of selection and compensation, but not for optimization strategy. This study contributes to the literature by demonstrating that HRM relates to employee outcomes through multiple pathways, which can be either universal or contingent.